THE MODERATING ROLE OF FINANCIAL TECHNOLOGY ON FINANCIAL AND ATTITUDE AND FINANCIAL MANAGEMENT BEHAVIOR:ANALYSIS OF MADURA’S CREATIVE EVONOMY PERFORMANCE - Pungky Setyawan, Silvia; Purnamawati, Purnamawati; Boy Singgih Gitayuda, M. (JURNAL EKBIS, 2024)
The printing industry plays an important role in the economy, covering publishing, graphic design, and advertising, as well as printing various products such as books, magazines, brochures, and promotional materials. However, challenges from technological developments and economic pressures have caused printing companies to face financial management problems. This study aims to examine the impact of financial attitudes and financial management actions on printing business performance, with fintech as a moderating variable. Financial attitudes refer to the views of business owners on financial management, while management actions include financial management behaviors and practices in the business. Business performance is measured through profitability, operational efficiency, and growth, and fintech can strengthen or weaken the relationship between the two.